2006
DOI: 10.1007/s10519-005-9027-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Memory Performance During Normal Aging: Twin Association Models of APOE and Other Alzheimer Candidate Genes

Abstract: The APOE gene (apolipoprotein E) is a major risk factor for Alzheimer's Disease (AD) but has been inconsistently associated with memory in nondemented adults. Two other genes with mixed support as genetic risk factors for AD, A2M (alpha-2-macroglobulin) and LRP (low-density lipoprotein receptor-related protein), have not been studied in relation to memory among nondemented adults. The present study examined these three genes and latent growth parameters estimated from memory performance spanning 13 years in 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
5
26
2
Order By: Relevance
“…These results echo the findings of a meta-analysis of cross-sectional studies by, 11 which concluded that, in the general aging population, the influence of apolipoprotein E genotype is small in magnitude and specific to certain domains of cognitive function. The findings of the current study, together with other, 11,15 but not all, 13,20 comparable observations, raise the possibility that apolipoprotein E 4 is a determinant of the trajectory of memory loss (and consequent cognitive decline) in the elderly general population. Table 1 for baseline models and Table 2 for change models.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results echo the findings of a meta-analysis of cross-sectional studies by, 11 which concluded that, in the general aging population, the influence of apolipoprotein E genotype is small in magnitude and specific to certain domains of cognitive function. The findings of the current study, together with other, 11,15 but not all, 13,20 comparable observations, raise the possibility that apolipoprotein E 4 is a determinant of the trajectory of memory loss (and consequent cognitive decline) in the elderly general population. Table 1 for baseline models and Table 2 for change models.…”
Section: Discussionsupporting
confidence: 77%
“…[10][11][12][13][14][15] The underlying mechanism is thought in part to be more beta-amyloid deposits in the presence of E 4 than with other isoforms of the apolipoprotein, 8,43 although it is increasingly clear that apolipoprotein E phenotype has multiple effects on neurobiology. 21 Alzheimer's disease, characterized by episodic memory loss, is likely to be the end result of a long subclinical degenerative process, and the question arises as to when and how apolipoprotein E 4 contributes to this less-obvious pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the former study the amplified decline was observed for e4 homozygotes, whereas in the present study we considered e4 heteroand homzygotes together for sample size considerations. Similarly, A2M and 5HTR2A were associated with mean differences in episodic figural recognition change over age (Thurstone Picture Memory) in prior studies (Reynolds, Jansson, et al, 2006;Reynolds, Prince, et al, 2006) but in the present case neither were identified as 'variability genes' for episodic figural recognition change.…”
Section: Discussionsupporting
confidence: 53%
“…Variation in DRD4 and COMT (a gene involved in metabolizing dopamine) is implicated in better attentional control and working memory performance, as well as stronger neural activation in these frontal regions. 79,80 In addition, although it has been studied in regards to dementia in adulthood, the APOE gene (apolipoprotein E) has been implicated in typical variation in adults' working memory performance as well 81,82 and may emerge as a gene that explains variation in working memory performance even in childhood.…”
Section: Self-regulation and Genetic Mechanismsmentioning
confidence: 99%